1999
DOI: 10.1080/07391102.1999.10508322
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Potentials of DNA. Comparative Analysis of Promoter and Nonpromoter Nucleotide Sequences

Abstract: Distribution of electrostatic potential of DNA fragments was evaluated. A method for calculation of electrostatic potential distribution based on Coulomb's law is proposed for long DNA fragments (approximately 1000 nucleotide pairs). For short DNA sequences, this technique provides a good correlation with the results obtained using Poisson-Boltzmann equation thus justifying its application in comparative studies for long DNA fragments. Calculation was performed for several DNA fragments from E. coli and bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
11
0
5
Order By: Relevance
“…Though the method cannot be applied for rigorous treatment, it is quite suitable for qualitative analysis of electrostatic map of natural DNA molecule and for comparative studies of its di®erent parts. 7 For further analysis, the two-dimensional distribution of the potential was averaged along the azimuthal angle to yield a one-dimensional pro¯le.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the method cannot be applied for rigorous treatment, it is quite suitable for qualitative analysis of electrostatic map of natural DNA molecule and for comparative studies of its di®erent parts. 7 For further analysis, the two-dimensional distribution of the potential was averaged along the azimuthal angle to yield a one-dimensional pro¯le.…”
Section: Methodsmentioning
confidence: 99%
“…We have suggested and used an approach to this problem based on the analysis of electrostatic properties of promoter DNA. Using the developed method for the whole-genome calculation of electrostatic potential distribution, 7 we revealed the general properties of genome DNA electrostatic potential pro¯le 7À10 and principles of its formation, 8 and explored the electrostatic properties of some genomes and the role of electrostatics in their functioning. 7À14 Studies of the general properties of genome DNA electrostatic potential pro¯le found that it correlates with the GC content, although it does not correspond to it exactly, and strongly depends on both the sequence arrangement and its context (°anking regions).…”
Section: Introductionmentioning
confidence: 99%
“…The protein effectively slides, onedimensionally, along the groove through a series of nonspecific binding events. The translocation mechanism for the nonspecific complex is not known, but is ATP-independent [25] and widely assumed to be driven by thermal motion. Other possible diffusion modes include "hopping", where a nonspecifically bound protein dissociates and re-associates within the same DNA domain.…”
Section: Protein Slidingmentioning
confidence: 99%
“…Finally the role of counterions in determining DNA structure such as bending and groove width [24] and affinity for such tracts is not yet fully understood. Sequence-dependent variations in the electrostatic surface of DNA may also present a unique "signature" in promoter regions [25].…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic potential distribution (EPD) around a DNA molecule seems to be the only physical property that could be recognized by other molecules from a distance. More than 10 years ago, a method for simple and fast calculation of EPD was proposed in our laboratory (Polozov et al, 1999). It is based on Coulomb formula and allows us to estimate the main EPD patterns for DNA sequences of a size of a whole prokaryotic genome.…”
mentioning
confidence: 99%